Moyamoya disease as a cause of intracranial haemorrhage in an infant: a case report - Maryam, Innama; Nadri, Gulnaz; Ali, M. Kashif; Afzal , Kamran (International Journal of Contemporary Pediatrics, 2024)
Moyamoya is a rare cerebrovascular condition characterized by progressive narrowing of large intracranial arteries leading to development of prominent arterial collaterals. These collateral vessels on angiography produce a smoky appearance termed as “moyamoya”, a Japanese word meaning puff of smoke in the air. Moyamoya disease usually presents as ischemic stroke in children and hemorrhagic stroke in adults. We present the story of an infant, term appropriate for gestational age with meconium aspiration syndrome, vigorous with hypoxic ischemic encephalopathy stage 1 (Sarnat with focal seizures involving right side of the body and severe anaemia, who was brought to our ER with complaints of vomiting and abnormal movements involving right side of the body. On examination severe pallor was observed, accompanied by a bulging anterior fontanelle, CT angiogram demonstrated marked attenuated calibre of left internal carotid artery in the supra-clinoid part A1 segment of anterior cerebral artery and middle cerebral artery with subacute infarct in middle cerebral artery territory suggestive of Moyamoya Disease. The infant was managed conservatively with one aliquot of packed red blood cells and antiepileptic drug phenobarbital. As our center is not equipped with neurosurgical interventions to be done in such patients, baby was referred to higher center for surgery. This case report serves as a reminder to consider Moyamoya disease in the differential diagnosis of infantile cerebral haemorrhage (stroke). Early diagnosis and prompt management are essential for improving outcomes in this rare and potentially devastating condition.